Media planning strategies and its internal and external factors at Kumpulan Media Karangkraf / Nur Alyani Mohd Shukri - Mohd Shukri, Nur Alyani (2014)
This study is to develop a strategy and offers strategic media planning formulations and recommendations. The research framework is analyzing the company’s external and internal factors of strategic media planning with the collaborations of SWOT analysis, which is Strengths, Weaknesses, Opportunities and Threats and sees the elements of media strategy. The study was conducted by using in-depth interviews of the Karangkraf employees in order to gain insights into the company media planning strategies. 3 informants from media marketing department and 3 informants from circulation department were interviewed based on the Strengths, Weaknesses, Opportunities and Threats of media planning in Karangkraf in order to identify the strategic plan development and the company sales. The findings shows Karangkraf s media planning is straightforward where the advantage of having 25 magazines. However, the strategic media planning development propose in this study are to stress on marketing mix, aggressive marketing and media planning procedure. There are specific strategies develop. This study includes a proposed strategic plan for Karangkraf s company as a guide to help develop media planning in future.